Toward the Virtual Benchmarking of Pneumatic Ventricular Assist Devices: Application of a Novel Fluid–Structure Interaction-Based Strategy to the Penn State 12 cc Device - Caimi, Alessandro (J Biomech Eng, 2017)
The pediatric use of pneumatic ventricular assist devices (VADs) as a bridge to heart transplant still suffers for short-term major complications such as bleeding and thromboembolism. Although numerical techniques are increasingly exploited to support the process of device optimization, an effective virtual benchmark is still lacking. Focusing on the 12 cc Penn State pneumatic VAD, we developed a novel fluid–structure interaction (FSI) model able to capture the device functioning, reproducing the mechanical interplay between the diaphragm, the blood chamber, and the pneumatic actuation. The FSI model included the diaphragm mechanical response from uniaxial tensile tests, realistic VAD pressure operative conditions from a dedicated mock loop system, and the behavior of VAD valves. Our FSI-based benchmark effectively captured the complexity of the diaphragm dynamics. During diastole, the initial slow diaphragm retraction in the air chamber was followed by a more rapid phase; asymmetries were noticed in the diaphragm configuration during its systolic inflation in the blood chamber. The FSI model also captured the major features of the device fluid dynamics. In particular, during diastole, a rotational wall washing pattern is promoted by the penetrating inlet jet with a low-velocity region located in the center of the device. Our numerical analysis of the 12 cc Penn State VAD points out the potential of the proposed FSI approach well resembling previous experimental evidences; if further tested and validated, it could be exploited as a virtual benchmark to deepen VAD-related complications and to support the ongoing optimization of pediatric devices.